Sentencing Disparity and Focal Concern: An Assessment of Judicial Decisions on Sha Zhu Pan Cases Collected From China Judgements Online - Wang, Fangzhou (Crime & delinquency, 2025)
Sha Zhu Pan (杀猪盘), or Pig-Butchering scam, is a new online romance scam that mainly targets Chinese-speaking individuals to gain emotional trust and persuade victims to invest in a fictitious website controlled by the scammer group. The substantial economic loss forced the Chinese government to launch a series of judicial campaigns against this crime. Regardless, Sha Zhu Pan has not been significantly curbed but intensified and spread from mainland China to Southeast Asia, North America, and other regions. When procuring answers to this conundrum, no empirical studies have attempted to explore judicial aspects among Sha Zhu Pan cases in China. The purpose of this paper is to utilize focal concern theory, a conceptual framework generally applies to explain sentencing disparity, to explore whether the sentencing of Sha Zhu Pan offenders is guided by legal factors outlined in Chinese sentencing guidelines. To answer this question, this study quantitatively analyzes 172 legal cases collected from China Judgments Online. Although few inconsistent findings exist, the empirical evidence reveals that the judgments in Sha Zhu Pan cases are primarily driven by the three legal elements of the focal concern theory. The outcomes expand the focal concern theory to cybercrime sentencing in a cross-cultural context while offering insights to guide future research.